New species of Tomocerus (Entomobryomorpha, Tomoceridae) with remarkable form of mucronal dorsal lamella - Yu, Daoyuan; Pan, Zhixiang; Shi, Shidi (Zootaxa, 2017)
Two new species of Tomocerus are described from Shaanxi and Gansu Provinces, China. Tomocerus nuwa sp. nov. and Tomocerus fuxi sp. nov. are similar to Tomocerus violaceus, Tomocerina yiliensis and Tomocerina tianshanensis mainly in the habitus and the basal formula of dental spines, but are different from the laters and most other known species of Tomocerinae mainly in the characteristic apical structure of mucronal dorsal lamella. Besides, these two species are similar to each other in the presence of only one typical bothriotrichum on Th. II, the number and position of ventral spine-like chaetae on tibiotarsi and the arrangement of dental spines on the basal subsegment of dens, but are different mainly in the chaetotaxy, the manubrial pseudopores and corner chaeta, and the arrangement of dental spines on the middle subsegment of dens.